Profissional waiter pramusaji ahli / Marsum Widjojo Atmodjo, Hj. Siti Fauziah ; editor, Fl. Sigit Suyantoro. - MARSUM WIDJOJO ATMODJO, H,1944-; Sigit Suyantoro, Fl.; Siti Fauziah, Hj. (Andi, 2016)
xiv, 418 hlm. : ilus. ; 23 cm